2015
DOI: 10.1016/j.ygyno.2015.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Fully-sialylated alpha-chain of complement 4-binding protein: Diagnostic utility for ovarian clear cell carcinoma

Abstract: Our study suggested that A2160 may be a useful biomarker to distinguish early-stage OCCC from endometrioma. This new biomarker can be potentially applied for the monitoring of endometrioma patients, making possible the early diagnosis of OCCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 18 publications
0
17
0
Order By: Relevance
“…Recent studies show that C4BPA is highly expressed in non-small cell lung cancer ( Liu et al , 2012 ). Furthermore, fully-sialylated C4BPA, A2160, is a newly identified serum biomarker for ovarian cancer, and interestingly, A2160 levels in patient sera are particularly useful for distinguishing early-stage clear cell carcinoma from endometrioma ( Mikami et al , 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies show that C4BPA is highly expressed in non-small cell lung cancer ( Liu et al , 2012 ). Furthermore, fully-sialylated C4BPA, A2160, is a newly identified serum biomarker for ovarian cancer, and interestingly, A2160 levels in patient sera are particularly useful for distinguishing early-stage clear cell carcinoma from endometrioma ( Mikami et al , 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Sera were prepared by previously described methods [ 26 , 27 ]. Briefly, 400 μL of cold acetone containing 10% trichloroacetic acid (Wako Pure Chemical Industries, Ltd., Osaka, Japan), and 50 μg of fetal calf fetuin (Sigma, St. Louis, MO, USA) as an internal standard, were added to 100 μL of patient sera, and mixed at − 20 °C for 90 min to remove serum albumin.…”
Section: Methodsmentioning
confidence: 99%
“…To establish a reliable and robust blood test for early-stage EOC detection, we developed a glycopeptide profiling technology using mass spectrometry, which detects aberrant serum sugar chains in patient sera [14]. In our previous studies, we have shown that C4-binding protein with fully sialylated sugar chains is specifically increased in the sera of EOC patients [15][16][17]. Based on this, we developed a comprehensive serum glycopeptide spectra analysis (CSGSA) technology by combining glycopeptide profiling with orthogonal partial least squares discriminant analysis (OPLS-DA) [18].…”
Section: Introductionmentioning
confidence: 99%